Teaching Speaking and The Teacher`s Role in EFL Learning amidst Emergency Remote Teaching - Fitriya Dessi Wulandari (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Teaching speaking in EFL learning nowadays confronts technical problems of having non face to face meeting. The condition of emergency remote teaching insists students adapting the condition of having online learning. Building the bridge of gasps, the presence of teacher`s role is significant. Confronting the problems, this study revealed teaching speaking and the teacher`s role in EFL Learning in non-English department class. The data were taken from online interview, self-written and observation then analyzed by data reduction, display and conclusion or verification. The research was taken on online class of Speech Therapy students which undergo on the online class group. The results showed that teaching speaking using video and voice note as media for teaching and learning successfully made the process occur effectively and meaningfully. The use of video stimulates students’ interest and motivation in learning the materials. Moreover, voice note be an effective media in practicing speaking, giving feedback and discussing. The result contributed to teachers and other researchers for selecting the suitable media in teaching and practicing speaking amidst the emergency remote teaching